P29 | GLUTAMATERGIC MODULATION OF HYPOTHALAMIC RSPONDIN3 NEURONS UNDER PHYSIOLOGICAL CONDITIONS (European Journal of Histochemistry)
Food intake is a complex behavior regulated by neuropeptides released from the central nervous system. R-spondin (Rspo) peptides are expressed at the mRNA level in hypothalamic regions involved in feeding behavior and play a role in appetite regulation1. The glutamatergic system, as a major excitatory neurotransmitter in the hypothalamus, regulates many endocrine and peptidergic systems2. However, there is limited information about neurotransmitter control of R-spondin neurons, and no data exist regarding glutamatergic modulation.This study investigated whether Rspo3-expressing hypothalamic neurons are activated after refeeding or glucose administration following 48 h of fasting, and whether this activation can be suppressed by glutamatergic antagonists. c-Fos was used as a neuronal activation marker. Sprague Dawley rats (5 males and 5 females per group) were divided into seven groups receiving combinations of fasting, refeeding, glucose, CNQX (2 mg/kg), or MK-801 (0.05 or 1 mg/kg). Coronal brain sections (40 μm) were processed for Rspo3/c-Fos immunoperoxidase labeling. Double-labeled neurons were quantified in SON, PVN, and ARC. Plasma Rspo3 levels were measured by ELISA. The percentage of activated Rspo3 neurons in SON, PVN, and ARC was respectively: fasting (♂1.53%, 6.54%, 7.95; ♀6.90%, 13.01%, 27.26), refeeding (♂93.67%, 75.72%, 1.11; ♀82.15%, 45.84%, 19.76), and CNQX+refeeding (♂9.24%, 9.34%, 2.74; ♀17.02%, 5.69%, 11.31). Glucose injection increased Rspo3 activation, which was suppressed by antagonist pretreatment (p<0.001). ELISA confirmed that refeeding elevated Rspo3 levels, which were reduced by CNQX to control-like values (p<0.05). Glucose protocols revealed significant group differences in both sexes (p<0.05). These findings show that refeeding or glucose activates Rspo3 neurons through glutamatergic mechanisms involving c-Fos, supported by peripheral ELISA data.